The burden of community-managed acute respiratory infections in the first 2-years of life - Sarna, Mohinder; Ware, R.; Sloots, T.; Nissen, M.; Grimwood, K.; Lambert, S. (Wiley-Liss, Inc, 2016)
© 2016 Wiley Periodicals, Inc. Background: Contemporary information on acute respiratory infections (ARIs) in children is based on hospital cohorts, primary healthcare presentations, and high-risk birth cohort studies. We describe the burden and determinants of symptomatic episodes of ARIs in unselected healthy infants in the first 2-years of life. Methods: One hundred and fifty-four infants from subtropical Brisbane, Australia participated in a longitudinal, community-based birth cohort study. A daily tick-box diary captured pre-defined respiratory symptoms. Parents also completed a burden diary, recording family physician and hospital visits, and antibiotic use. Results: Participants contributed 88,032 child-days (78.2% of expected), of which 17,316 (19.7%) days were symptomatic during 1,651 ARI episodes: incidence rate 0.56 ARIs per child-month (95%CI: 0.54, 0.59). Runny nose (14,220 days; 6.0-days median duration) and dry cough (6,880 days; 4.0-days median duration) were reported most frequently. Overall, 955 burden diaries recorded 455 family physician visits (1–8 visits per ARI) and 48 hospital presentations, including six hospital admissions. Antibiotics were prescribed on 209 occasions (21.9% of ARI episodes where burden diary submitted). Increasing age, non-summer seasons, and attendance at childcare were associated with an increased risk of ARI. Conclusions: ARIs are a common cause of morbidity in the first 2-years of life, with children experiencing 13 discrete ARI episodes and almost 5-months of respiratory symptoms. Most ARIs are managed in the community by parents and family physicians. Antibiotic prescribing remains common for ARIs in young children. Secular societal changes, including greater use of childcare in early childhood, may have maintained the high ARI incidence in this age-group. Pediatr Pulmonol. 2016;51:1336–1346. © 2016 Wiley Periodicals, Inc.